2016
DOI: 10.1021/acs.energyfuels.6b02428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2O Addition on Oil Sand Bitumen Cracking Using a CeO2–ZrO2–Al2O3–FeOx Catalyst

Abstract: The behavior of a CeO 2 −ZrO 2 −Al 2 O 3 −FeO x catalyst typically employed during heavy oil decomposition was investigated in conjunction with the addition of H 2 O, as a means of improving the upgrading activity and suppressing coke formation on the catalyst. The upgrading of oil sand bitumen diluted with benzene was examined with this catalyst at various F H 2 O /F bitumen ratios [where F H 2 O is the water flow rate (g h −1 ) and F bitumen is the bitumen feedstock flow rate (g h −1 )] in a fixedbed flow-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The molecular weight distributions of the bitumen and oil product from HPLC were converted into carbon number distributions by assuming the unit structure of heavy oil as _ CH2 _ . The product yield was divided into three groups according to the carbon number: gas oil (Gas Oil, carbon numbers 14-20), vacuum gas oil (VGO, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and vacuum residual oil (VR, 41). Carbonaceous solid deposited on the reactor wall was designated as residue, and coke deposited on the surface of the catalyst was analyzed with an elemental analyzer.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight distributions of the bitumen and oil product from HPLC were converted into carbon number distributions by assuming the unit structure of heavy oil as _ CH2 _ . The product yield was divided into three groups according to the carbon number: gas oil (Gas Oil, carbon numbers 14-20), vacuum gas oil (VGO, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and vacuum residual oil (VR, 41). Carbonaceous solid deposited on the reactor wall was designated as residue, and coke deposited on the surface of the catalyst was analyzed with an elemental analyzer.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Water 34) The iron-based oxide catalysts are assumed to consume lattice oxygen during the decomposition of heavy oil, which is replaced by active oxygen species from water, resulting in retained catalytic activity and stable structure, as discussed in section 1. 3.…”
Section: Clarification Of Reaction Cycle Over Ironbased Oxide Catalyst Using Heavy Oxygenatedmentioning
confidence: 99%
“…Parkinson et al found that water was decomposed on the surface of Fe 3 O 4 by scanning tunneling microscope at room temperature. Kondoh et al used Ce, Al, and Zr doped Fe 2 O 3 as catalysts for steam catalytic cracking of oil sand bitumen. They found that the light oil yield reached 71 %.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10 % of the oxygen species were incorporated into the product oil, and the remaining 90 % were converted to carbon dioxide 13) . Part of the carbon dioxide was derived from steam in the cracking of heavy oil with iron oxide-based catalyst as demonstrated using heavy oxygenated water 20) . Generation of oxygen-containing compounds was confirmed by the catalytic cracking of a model compound 14) .…”
mentioning
confidence: 99%